Nivel de estrés auto percibido y síntomas asociados de los domiciliarios por plataformas tecnológicas en Bogotá (2022)
Stress is a problem where people in the world are affected, among which digital platform workers in Colombia stand out, generating physiological, social behavior, psycho-emotional, intellectual, and labor symptoms. Objective: To determine the level of self-perceived stress associated with the work of domiciles by technological platforms in Bogotá. Materials and methods: Quantitative, descriptive cross-sectional study, with conglomerate sampling, a sociodemographic record was used, the instrument of social, economic, labor information and conditions of the development of the activity on the platform of the International Labor Organization and for the evaluation of the stress of the Ministry of Social Protection containing four types of symptoms and a self-perceived stress question associated with work using a Likert scale. All information is processed with Excel. Results: 386 people participated in the study, where 13.4% (n=52) were of Colombian nationality and the remaining 86.5% (n=334) of Venezuelan nationality, with moderate levels of stress and presentation of several related symptoms. with the stress of working as domiciles on platforms. Conclusion: A moderate level of self-perceived stress was found in most of the population, and they are men; people in common law union, socioeconomic stratum 7 3 and Venezuelan nationality who are most stressed. The most frequent symptoms are physical and working conditions are informal and uncertain